Effects of a DVD-delivered mindfulness-based intervention for stress reduction in medical students: a randomized controlled study - Phang, Cheng Kar; Mukhtar, Firdaus; Ibrahim, Normala; Keng, Shian-Ling; Mohd. Sidik, Sherina (Penerbit Universiti Sains Malaysia and Malaysian Association of Education in Medicine and Health Sciences (MAEMHS), 2015)
The aim of this study was to evaluate the effects of a DVD-delivered mindfulness-based intervention for reducing stress among medical students in a Malaysian university. Methods: A total of 76 medical students participated in the intervention program (Mindful-Gym DVD). They were stratified according to year of studies and randomly allocated to intervention (N = 38) and control groups (N = 38). The following outcome variables were measured at pre- and post-intervention: mindfulness (with Mindful Attention Awareness Scale, MAAS); perceived stress (with Perceived Stress Scale, PSS); mental distress (with Depression, Anxiety and Stress Scale, DASS); and self-efficacy (with General Self-efficacy Scale, GSE). Hierarchical multiple regression analyses were used to analyse the effect of group (Intervention vs. Control) on changes in the outcome variables. Results: One week after the intervention, participants in the intervention group reported significantly greater improvements with small to medium effect sizes in self-reported levels of mindfulness (β = 0.19, ∆R2 = 0.04, p = 0.028, f 2 = 0.07), perceived stress (β = -0.25, ∆R2 = 0.06, p = 0.006, f 2 = 0.11), mental distress (β = -0.27, ∆R2 = 0.07, p = 0.003, f 2 = 0.13), and self-efficacy (β = 0.27, ∆R2 = 0.07, p = 0.003, f 2 = 0.13), compared to participants in the control group. The number needed to treat (NNT) to achieve ‘normal’ levels of depressive, anxiety, and stress symptoms (as indicated by the DASS scores) were 5, 8, and 6 respectively. Conclusions: This study found that the DVD-delivered mindfulness-based program is potentially a labour- and cost-effective and easily accessible stress reduction program for medical students.